TANTANGAN DAN PELUANG DALAM PENELITIAN PEMIKIRAN TOKOH: STUDI INTEGRASI TEORI SEJARAH LISAN DAN MASLAHAH - Sugitanata, Arif; Suud Sarim Karimullah; Siti Aminah; Muhammad Hasyied Abdurrasyied (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2024)
This study aims to identify and analyze the challenges and opportunities in scientific research on the thoughts of both living and deceased figures, utilizing the framework of oral history theory and the theory of maslahah. Through a qualitative research approach based on literature studies, this research demonstrates that when studying living figures, researchers benefit from direct access through in-depth interviews, allowing for the collection of rich and contextual primary data. However, the primary challenge lies in the potential bias of respondents, which can affect the validity of the research findings. Conversely, research on deceased figures offers data stability from unchanging secondary sources, though the limitation of access to direct clarification poses a significant challenge. In light of this, the analysis of ral history theory highlights the importance of direct interviews in understanding the experiences of living subjects, while maslahah theory provides ethical guidance in considering the social impact and general welfare resulting from this research. The analysis based on these two theories indicates that scientific research on figures, whether living or deceased, requires a structured and ethical approach to produce meaningful contributions to the development of knowledge and society. This study suggests the need for special attention to the selection of methodology and the application of rigorous research ethics to ensure the validity and utility of research outcomes, and recommends further support for more in-depth research in this context. Consequently, this research not only enriches the academic literature but also provides critical insights into the role of figures in history and thought, as well as their relevance to contemporary challenges and needs.